2013
DOI: 10.1111/jwas.12024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Carbohydrate‐to‐lipid Ratios on Growth Performance, Body Composition, Hepatic Enzyme Activities, and Digestive Enzyme Activities of Juvenile Australian Redclaw Crayfish, Cherax quadricarinatus (von Martens)

Abstract: A growth experiment was conducted to determine the optimal dietary carbohydrate-to-lipid (CHO : L) ratio for the Australian redclaw crayfish, Cherax quadricarinatus (von Martens). Specimens were divided into five treatment groups and fed twice a day to apparent satiation with isonitrogenous and isoenergetic diets with dietary CHO : L ratios of 10.75:1, 5.99:1, 3.60:1, 2.18:1, or 1.33:1. Over the 8-wk growth trial, redclaw crayfish fed the 2.81:1 and 3.60:1 diets exhibited better weight gain (WG), specific grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
(75 reference statements)
1
16
1
Order By: Relevance
“…In this study, hepatopancreatic HK activity and mRNA expression increased significantly as the dietary carbohydrate level was increased. As reported for M. nipponense , redclaw crayfish fed a high‐carbohydrate diet show increased HK activity (Zhu et al., ). In contrast, HK activity is low in L. vannamei and not affected by the dietary carbohydrate level (Rosas et al., ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In this study, hepatopancreatic HK activity and mRNA expression increased significantly as the dietary carbohydrate level was increased. As reported for M. nipponense , redclaw crayfish fed a high‐carbohydrate diet show increased HK activity (Zhu et al., ). In contrast, HK activity is low in L. vannamei and not affected by the dietary carbohydrate level (Rosas et al., ).…”
Section: Discussionsupporting
confidence: 64%
“…However, Shiau and Peng () reported that starch can replace some dietary protein in the P. monodon diet. A study on juvenile Cherax quadricarinatus showed that maximum weight gain and the best feed conversion rate were obtained when the crayfish were fed the optimal dietary carbohydrate‐to‐lipid ratio (Zhu et al., ). A dietary cornstarch level of 203 g kg –1 was appropriate for juvenile Procambarus clarkii fed several isonitrogenous practical diets (Xiao et al., ), and 100–200 g kg –1 was the optimal cornstarch level for Litopenaeus vannamei fed diets containing different levels of corn starch balanced with cellulose (Guo, Liu, Tian, & Huang, ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, this country accounted for 1.19 million tonnes of the total global production amounting to 2.6 million tonnes (Food & Agriculture Organisation; FAO, ). High levels of worldwide production of P. hypophthalmus have increased the demand for appropriate and cost‐effective feeding and reinforced the importance of carbohydrates (CHO) as the most inexpensive energy sources in the fish diet (Tran‐Duy, Smit, Van Dam, & Schrama, ; Zhu et al, ). Carbohydrates serve as an important source of energy in most mammals, but their function is limited in fish, particularly in carnivorous species (Stone, ; Wilson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the digestive enzyme pattern can reflect some aspects of the nutritional physiology, and this information was applied to determine growth that can also be useful for the diet formulation (Debnath, Pal, Sahu, & Yengkokpam, ; Tongprajjukae & Kovitvadhi, ). Several studies have reported the effects of carbohydrate levels on digestive enzymes in different fish species (Correa, Aguiar, Lundstedt, & Moraes, ; Kumar, Sahu, Pal, & Kumar, ; Tian et al., ; Zhu et al., ), and some studies have been conducted to appraise the nutritional requirements of Kutum. Mahmoodi, Noverian, Falahatkar, and Khoshkholgh () reported that a diet containing 35% protein with 14% lipid would be suitable for optimum growth of Caspian Kutum juveniles.…”
Section: Introductionmentioning
confidence: 99%